THE INCREASE IN POVERTY IN THE WORLD AND THE NATURAL, ECONOMIC, SOCIO-GEOGRAPHICAL FACTORS AFFECTING IT - Kamolov Elbek Sherali o‘g‘li; Mavlonova Shalola Anvar qizi; Ergasheva Gulshoda Imon qizi (Web of Journals Publishing, 2025)
This article examines the factors affecting poverty and their characteristics. Also, issues of increasing poverty under the influence of natural, economic-social and non-geographical factors are revealed.
Keywords: Poverty, natural-geographic factors, socio-economic geographic factors, inflation, climate change, poverty and environment.